A critical appraisal of research in arts, health and wellbeing - Clift, Stephen; Kreutz, Gunter; Pritchard, Stephen; Tan, Michael; Lehikoinen, Kai; De Quadros, Andre; Coren, Esther; Phillips, Kate (Frontiers, 2023)
The field of ‘Arts, Health and Wellbeing,’ has witnessed a remarkable growth of interest over the last 20 years. Seminal work has been produced from the beginning of the millennium, which has led to the emergence of the arts and music as topics in health science beyond therapy. Arts and musical activities for health have been explored in contexts including treatment of acute and long-term conditions, health prevention, health literacy, and health promotion. Researchers, health professionals, and arts and music practitioners in the UK, Australia, the United States, Europe, and the Nordic countries have been at the forefront of this growing movement, but interest now extends more widely internationally, emerging literature from China, India, Singapore and a number of African states.
Keywords: taide; hyvinvointi; terveys; musiikki